Harnessing ICTs : a Canadian First Nations experience; introduction to K-Net - Ramirez, Ricardo; Aitkin, Helen; Jamieson, R.; Richardson, D. (IDRC, Ottawa, ON, CA, 2003)
Spanish version available in IDRC Digital Library: Cómo aprovechar las TICs : una experiencia de las Primeras Naciones Canadienses; introducción a K-Net This document is an introduction to the work of K-Net, a program of Keewaytinook Okimakanak (KO) tribal council. K-Net is providing information and communication technologies (ICTs) to First Nations communities in remote regions of northwestern. Ontario, Canada. In less than a decade, KO communities have experienced a major technological transformation, and this case study series outlines some of the key lessons learned from their experience.